Digitally Smart Generation, Character-Driven Generation: Educational Challenges in the Society 5.0 Era - Desy Ratnasari; Muhammad Robeth Najh; Angelina Dwi Rahma; Kartika Yuni Purwanti (International Forum of Researchers and Lecturers, 2026)
The rapid advancement of technology in the Society 5.0 era necessitates a fundamental shift in primary education, emphasizing not only technological proficiency but also robust moral foundations. This study explores the integration of digital literacy and character education in elementary schools, addressing the unique challenges and opportunities presented by a human-centered, super-smart society. Utilizing a systematic literature review and qualitative meta-synthesis of global educational practices over the last five years, this research investigates how primary education frameworks must adapt to foster a digitally intelligent yet character-driven generation. The findings reveal that while digital tools enhance interactive learning, there is a critical gap in ethical digital navigation among young learners. The discussion highlights that successful educational models in Society 5.0 require a tripartite approach: continuous pedagogical innovation, targeted digital upskilling for teachers, and active parental involvement. Furthermore, a comparison with traditional educational models demonstrates that modern character education must seamlessly encompass digital citizenship, cyberbullying prevention, and empathy in virtual environments. The study concludes that building a morally grounded generation demands holistic curriculum reforms that embed character values directly into digital literacy instruction, rather than treating them as separate entities.